Outer Synchronization of a Modified Quorum-Sensing Network via Adaptive Control. (9th August 2018) - Zhang, Jianbao; Zhang, Wenyin; Zhang, Denghua; Yang, Chengdong; Zhu, Kongwei; Qiu, Jianlong
Abstract : Motivated by the quorum-sensing mechanism of bacteria, this paper modifies the network model by adding unknown parameters and noise disturbances and investigates the problem of outer synchronization via adaptive control. In case there exist three unknown parameters, updating laws are presented to identify the unknown parameters with help of Lyapunov stability theory, and the negative effects of noise disturbances are also compensated by designing adaptive controllers. In addition, we simplify the obtained conditions and carry out two succinct and utilitarian corollaries. Finally, numerical simulations are provided to show the validity of the obtained results.